Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: multiply... (4x+4)(6x^2 +8x+3)
A: (4x+4)(6x^2 +8x+3) = 24x^3 + 56x^2 + 44x + 12
Get an answer
Original conversation
User: multiply... (4x+4)(6x^2 +8x+3)





Weegy: a. Factor as: (x - 3)(x + 1)^3 = 0 zeros are at x = 3 and x = -1 y ' = 4x^3 - 12x - 8 4(x - 2)(x + 1)^2 zeros at x = 2 and x = -1 - - - - - - - - - - - - - - - - - - - - b. y " = 12x^2 - 12 y "(2) = 36 which is positive, [ so x = 2 is a minimum point y "(-1) = 0, an inflection point - - - - - - - - - - - - - - - - - - - - c. f(x) decreases from [-8, 2] and increases from [2, +8] - - - - - - - - - - - - - - - - - - - - d. f(x) is negative for x = [-1, 3] and positive for all other real values ]
Expert answered|LeighaI|Points 0|

Question
Asked 3/20/2012 9:32:07 AM
Updated 3/21/2012 11:26:01 AM
3 Answers/Comments
This conversation has been flagged as incorrect.
New answers
Rating
3
(4x+4)(6x^2 +8x+3) = 24x^3 + 56x^2 + 44x + 12
Added 3/20/2012 10:42:09 AM
This answer has been confirmed as correct and helpful.
Unflagged by andrewpallarca [7/7/2014 7:25:01 PM], Confirmed by andrewpallarca [7/7/2014 7:25:03 PM]
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
solve for v.... 6/v=9/v-1/2
Weegy: The answer is v = 4. :) User: solve for b.... b^2 - 6b - 7=0 (More)
Question
Expert Answered
Updated 9/20/2014 10:57:20 PM
2 Answers/Comments
6/v=9/v-1/2
6/v - 9/v = -1/2
-3/v = -1/2
v = -3/( -1/2)
v= -3 *(-2)
v = 6
Added 9/20/2014 10:56:18 PM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [9/20/2014 11:00:45 PM]
b^2 - 6b - 7=0
(b - 7)(b + 1) = 0
b = 7 or b = -1.
Added 9/20/2014 10:57:20 PM
factor completely... 4x^8 - 12x^7 + 24x^6
Weegy: 4x^8 - 12x^7 + 24x^6 = 4x^6 (x^2 - 3x + 6) (More)
Question
Expert Answered
Updated 7/11/2014 12:10:08 AM
0 Answers/Comments
subract the polynomials (-9s^2 + 5s + 2) - (7s^2 + 2)
Weegy: (-9s^2 + 5s + 2)- (7s^2 + 2) = (-9s^2 + 5s + 2) + (-7s^2 - 2) = -16s^2 + 5s (More)
Question
Expert Answered
Updated 122 days ago|2/16/2018 1:30:28 PM
0 Answers/Comments
factor the trinomial. a^3 - 2a^2 -15a
Question
Not Answered
Updated 110 days ago|2/28/2018 7:46:02 PM
1 Answer/Comment
a^3 - 2a^2 -15a
= a(a^2 - 2a - 15)
= a(a + 3)(a - 5)
Added 110 days ago|2/28/2018 7:46:02 PM
This answer has been confirmed as correct and helpful.
multiply and simplify. assumer variables represent nonzero real numbers... (x^18)(x^0)
Weegy: (x^18)(x^0) = x^18 (More)
Question
Expert Answered
Updated 6/16/2014 12:27:59 PM
1 Answer/Comment
I'm the only one getting negative ratings on these math questions. I get the feeling someone is fishing for my account.
Added 3/20/2012 2:47:01 PM
26,998,496 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
Popular Conversations
True or false? Stress has an effect on every system of the body.
Weegy: what is the question?
6/14/2018 12:05:59 PM| 2 Answers
What's 3 * 4
Weegy: Synonyms for the word "say" which are bigger in length and in impact, are communicate, ...
6/16/2018 8:51:59 PM| 2 Answers
S
L
Points 240 [Total 258] Ratings 0 Comments 170 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 115 [Total 266] Ratings 1 Comments 5 Invitations 10 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 1 Comments 0 Invitations 1 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.